On the Neotropical spider genera Enna O. Pickard-Cambridge, 1897 and Syntrechalea F. O. Pickard-Cambridge, 1902 (Araneae, Lycosoidea, Trechaleidae): descriptions, taxonomic notes and new records - Da Silva, Estevam L. Cruz; Viquez, Carlos; Lise, Arno A. (Zootaxa, 2012)
Two new species of the spider genus Enna O. Pickard-Cambridge, 1897 from Costa Rica and Peru are described and illustrated:Enna osaensis sp. nov. (female, Costa Rica) and E. moyobamba sp. nov. (female, Peru). The male of E. chickeringi Silva, Lise& Carico, 2008, from Costa Rica, is described and illustrated for the first time. Enna huarinilla Silva, Lise & Carico, 2008 is ajunior synonym of Enna caliensis Silva, Lise & Carico, 2008. Enna baeza Silva, Lise & Carico, 2008, E. bonaldoi Silva, Lise& Carico, 2008, E. igarape Silva, Lise & Carico, 2008 and E. trivittata Silva & Lise, 2009 are newly recorded from Peru. Par-adossenus junin Carico & Silva, 2010 is transferred to Enna O. Pickard-Cambridge, 1897. Trechalea boliviensis Carico, 1993and Trechalea lomalinda Carico, 1993 are transferred to Syntrechalea F.O.P.-Cambridge, 1902. New records of Syntrechalea lomalinda comb. nov. are reported to Venezuela and Brazil.